PMMA BONE CEMENT WITH L-ARGININE/NANO FISH BONE NANOCOMPLEX TO GENERATE APATIT FORMATION - Aurel Khoman, Gessica
Apatite growth is a bone regeneration approach to optimize bone repair and restore bone function. Generally, this property is owned by hydroxyapatite which can be taken from fish bone waste. In this study, apatite growth was observed in nano fish bone (NFB) processed from fish bone waste and used in PMMA bone cement. The resulting NFB has a Ca:P content of 1.65 with a particle size of 757.5 nm. PMMA was synthesized using emulsion polymerization method and by variating the SDS surfactant content to control particle size and uniformity. PSA characterization showed that the addition of SDS could reduce the particle size, from 102.8 nm in the absence of SDS addition to 42.1 nm with the addition of 5 wt% SDS. SEM characterization showed agglomeration due to very small particle size at the addition of 5 wt% SDS. PMMA is also added with L-Arginine to increase the biocompatibility and antibiotic properties of bone cement. Bone cement samples were tested for tensile strength which resulted in a decrease on tensile strength when added with NFB and L-Arginine. All bone cement samples with variations of added surfactant and BC-PMMA-1-NFB/L-Arg had better tensile strength than commercial PMMA. The immersion test showed that there was an increase in mass after immersion in the SBF solution for 7 days, which indicates the possibility of the formation of an apatite layer.